Nickel phosphate nanorod-enhanced polyethylene oxide-based composite polymer electrolytes for solid-state lithium batteries - Wu, Zhijun; Xie, Zhengkun; Yoshida, Akihiro; Wang, Jing; Yu, Tao; Wang, Zhongde; Hao, Xiaogang; Abudula, Abuliti; Guan, Guoqing (Journal of colloid and interface science, 2020)
[Display omitted] •PEO-LiTFSI-3%VSB-5 electrolyte exhibits high conductivity of 4.83 × 10−5 S·cm−1 at 30 °C.•PEO-LiTFSI-3%VSB-5 electrolyte shows better interface stability with lithium.•The batteries with PEO-LiTFSI-3%VSB-5 exhibit excellent electrochemical property.•VSB-5 can change the polymer arrangement and decrease the crystallinity. Solid-state electrolytes with high ionic conductivity, large electrochemical window, and excellent stability with lithium electrode are needed for high-energy solid-state lithium batteries. In this work, a novel polyethylene oxide (PEO)-Lithium bis(trifluoromethylsulphonyl)imide (LiTFSI)-nanocomposite-based polymer electrolyte was prepared by using nickel phosphate (VSB-5) nanorods as the filler. The ionic conductivity of the obtained PEO-LiTFSI-3%VSB-5 solid polymer electrolyte was found to be as high as 4.83 × 10−5 S·cm−1 at 30 °C and electrochemically stable up to about 4.13 V versus Li/Li+. The enhanced ionic conductivity was attributed to the reduced crystallinity of the PEO and the interaction between VSB and 5 and PEO-LiTFSI. In addition, the solid polymer electrolyte exhibited improved compatibility to the lithium metal anode with excellent suppression of lithium dendrites. The assembled LiFePO4/Li battery with the PEO-LiTFSI-3%VSB-5 solid polymer electrolyte showed better rate performance and higher cyclic stability than the PEO-LiTFSI electrolyte. It is demonstrated that this new solid polymer hybrid should be a promising electrolyte applied in solid state batteries with lithium metal electrode.